Informal caregivers in Germany – who are they and which risks and resources do they have? - Fuchs, Judith; Gaertner, Beate; Rommel, Alexander; Starker, Anne (Frontiers in Public Health, 2023)
Background The aim of this study is to describe the social characteristics, the health and living situation and the prevalence of behavioral risk factors of adult informal caregivers compared to non-caregivers in Germany. Methods We used data from the German Health Update (GEDA 2019/2020-EHIS survey) which is a cross-sectional population-based health interview survey conducted between 04/2019 and 09/2020. The sample comprised 22,646 adults living in private households. Three mutually exclusive groups of providing informal care or assistance were differentiated: intense caregivers (informal care ≥10 h/week), less-intense caregivers (informal care<10 h/week) and non-caregivers. For the three groups weighted prevalences of social characteristics, health status (self-perceived health, health-related activity limitations, chronic diseases, low back disorder or other chronic back defect, depressive symptoms), behavioral risk factors (at-risk drinking, current smoking, insufficient physical activity, non-daily fruit and vegetable consumption, obesity) and social risk factors (single household, low social support) were calculated and stratified by gender. Separate regression analyses adjusted for age-group were conducted to identify significant differences between intense and less-intense caregivers vs. non-caregivers, respectively. Results Overall, 6.5% were intense caregivers, 15.2% less-intense caregivers and 78.3% non-caregivers. Women provided care more often (23.9%) than men (19.3%). Informal care was most frequently provided in the age group of 45 to 64 years. Intense caregivers reported worse health status, were more often current smokers, physical inactive, obese and lived less often alone than non-caregivers. However, in age-group adjusted regression analyses only few significant differences were seen: Female and male intense caregivers had more often a low back disorder and lived less often alone compared to non-caregivers. In addition, male intense care-givers reported more often worse self-perceived health, health-related activity limitation, and the presence of chronic diseases. In contrast, less-intense caregivers and non-caregivers differed in favor of the less-intense caregivers. Discussion A substantial proportion of the adult German population provides informal care regularly, especially women. Intense caregivers are a vulnerable group for negative health outcomes, especially men. In particular measures to prevent low back disorder should be provided. As the necessity of providing informal care will probably increase in the future, this will be important for the society and public health.